2019
DOI: 10.1245/s10434-019-07316-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Esophageal Cancer Surgery in Terms of Surgical Approach and Extent of Lymphadenectomy: Findings of an International Survey

Abstract: Introduction Esophagectomy and lymphadenectomy are essential parts of the multimodal treatment of esophageal carcinoma with curative intent. Treatment regimens vary globally and are subject to debate. A global survey was designed to gain insight into current practice. Methods Fifty-seven international expert upper gastrointestinal surgeons received a personal invitation to participate in the survey, which focused on demographics and experience; extent of lymphadenectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…6 Ten years later in 2019, results from an international survey still indicated that there was no uniform, worldwide strategy for surgical treatment of EC. 7 Additionally, given the growing recognition that even after being clinically well staged using ultrasound, some T 2 N 0 esophageal cancers (between 20-25%) may be upstaged to pathologic T 3 and/or lymph node-positive disease; thus, numerous patients could be referred for postoperative therapy for TESCC. 8 Compared with the classic combination of 5-Fu and cisplatin (DDP) with RT for EC, preclinical data have shown that paclitaxel (PTX) could enhance the radiation sensitivity of tumor cells, potentiate the antitumor response rate and increase the therapeutic ratio of RT.…”
Section: Introductionmentioning
confidence: 99%
“…6 Ten years later in 2019, results from an international survey still indicated that there was no uniform, worldwide strategy for surgical treatment of EC. 7 Additionally, given the growing recognition that even after being clinically well staged using ultrasound, some T 2 N 0 esophageal cancers (between 20-25%) may be upstaged to pathologic T 3 and/or lymph node-positive disease; thus, numerous patients could be referred for postoperative therapy for TESCC. 8 Compared with the classic combination of 5-Fu and cisplatin (DDP) with RT for EC, preclinical data have shown that paclitaxel (PTX) could enhance the radiation sensitivity of tumor cells, potentiate the antitumor response rate and increase the therapeutic ratio of RT.…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, among other countries, curative treatment for patients with esophageal carcinoma consists of neoadjuvant chemoradiation followed by surgery [21, 22]. The radiation field during neoadjuvant treatment and the lymphadenectomy during surgery depend on the location of lymph node metastases but no consensus has been reached on the extent of the lymphadenectomy [23]. If a distribution pattern of lymph node metastases of esophageal carcinoma can be identified, the optimal neoadjuvant and surgical treatment can be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in pathologic types, surgical practices, and nominalization of LN stations have existed in different countries, even among different surgeons. 12 The N stage is determined by the number of positive LNs in the AJCC/UICC TNM classification system for EC, but there are no principles for the extent of LN dissection. 38 The Japan Esophageal Society has proposed a more precise but complex N staging system, in which regional LNs are divided into N1-N3 levels according to different stations.…”
Section: The Extent Of Ln Dissection For Thoracic Esccmentioning
confidence: 99%
“…However, until now, there has been no widely accepted LN dissection mode for EC worldwide because different pathological types of ECs have different oncobiological features and different patterns of LN metastasis. 12 Before the 1980s, esophagectomy was performed through the right or left thoracotomies with two-field lymphadenectomy (2FL), including thoracic and upper abdominal LNs. Both in Japan and China, it was reported that postoperative recurrences were frequently found in the cervicothoracic region.…”
Section: Introductionmentioning
confidence: 99%